Unveiling The Burden of Anaemia: Socio-Demographic and Obstetric Determinants Among Pregnant Women in Mehsana District, Gujarat - Nitin Lodha; Hitesh Bhabhor; Ullas Bhabhor; Jayna Devalia; Jatin Chhaya (National Journal of Medical Research)
Background: Anemia is a leading contributor to maternal mortality in India. Early identification and timely intervention during pregnancy can help prevent adverse health outcomes. This study aimed to estimate the prevalence of anaemia among pregnant women and identify associated socio-demographic and obstetric factors.